A Novel COL7A1 Mutation in a Patient With Dystrophic Epidermolysis Bullosa. Successful Treatment With Upadacitinib - Lai S; Lin C; Guo Z; Lai Y; Xie L; Wan C; Yang T; Li L (Clinical, Cosmetic and Investigational Dermatology)
Shuqin Lai,* Chunli Lin,* Zimeng Guo, Yun Lai, Ling Xie, Chunlei Wan, Tao Yang, Longnian Li Department of Dermatology, Candidate Branch of National Clinical Research Centre for Skin and Immune Diseases, First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Tao Yang; Longnian Li, Department of Dermatology, Candidate Branch of National Clinical Research Centre for Skin and Immune Diseases, First Affiliated Hospital of Gannan Medical University, Ganzhou, 341000, People’s Republic of China, Email danny20021068@126.com; li_longnian@foxmail.comAbstract: Dystrophic epidermolysis bullosa (DEB) is a heterogeneous and rare genetic skin disease caused by mutations in the COL7A1 gene, which encodes Type VII collagen. The absence or dysfunction of Type VII collagen can cause the dense lower layer of the basal membrane zone of the skin to separate from the dermis, leading to blister formation and various complications. In different DEB subtypes, the severity of the phenotype is associated, to some extent, with the outcome of Type VII collagen caused by mutations in the COL7A1 gene, which may be reduced in expression, remarkably reduced, or completely absent. Here, we report a case of DEB caused by a mutation in the COL7A1 gene at a novel site, where the patient achieved favorable outcomes after treatment with upadacitinib. This study further expands the known COL7A1 gene mutation sites in the DEB subtype, providing new data for understanding the genotype-phenotype correlation and treatment of this disease.Keywords: dystrophic epidermolysis bullosa, COL7A1, type VII collagen, gene mutation, gene detection